The unintended consequences of interregionalism : effects on regional actors, societies and structures - Lopez Lucia, Elisa; Mattheis, Frank (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This edited book brings a new analytical angle to the study of comparative regionalism by focussing on the unintended consequences of interregional relations. The book satisfies the need to go beyond the consideration of the success or failure of international policies. It sheds light on complex interactions involving multiple actors, individual and institutional, driven by various representations, interests, and strategies, and which often result in unintended consequences that powerfully affect the socio-political context in which they unfold. By providing a new conceptual framework to understand how interregionalism brings about social change, the book examines the effects on the individual and institutional actors of interregional relations, and the effects on the social structures that constitute interregionalism. It also examines interregionalism's transformational character for structures of regional and international governance, as well as societies. This book will be of key interest to scholars and students in the fields of comparative regionalism, interregionalism, EU studies, international and regional organisations, global governance and more broadly to international relations, international politics and (comparative) area studies"--
The unintended consequences of interregionalism : new concepts for understanding theentanglements of regionalisms / Elisa Lopez Lucia and Frank Mattheis -- Overlapping regionalism and the unintended consequences of democracy clauses in the Americas / Haroldo Ramanzini Junior -- The unintended consequences of interregionalism on actorness of the European Union : the case of EU-ASEAN cooperation in disaster management / Giulia Tercovich -- The EU-CELAC Cooperation Programme on Drugs Policies and the unintended consequences of interregional interactions / Carolina Salgado -- The ASEAN way versus EU maritime multilateralism : the unintended consequences of EU-ASEAN maritime security cooperation / Dominik Giese -- Between bilateralism and interregionalism : EU-Brazil strategic partnership and the unintended consequences for EU-MERCOSUR relations / Bruno Theodoro Luciano -- The unintended consequences of regional security cooperation in West Africa-EU relations beyond the African Peace and Security Architecture / Friedrich Plank -- The Sahel as an unintended region : competing regionalisms and insecurity dynamics / Edoardo Baldaro -- Agential constructivism, shadow regionalisms and interregional dynamics in the Horn of Africa / J. Andrew Grant, Abdiasis Issa, and Badriyya Yusuf -- When external drivers of regional integration turn into actors of regional disintegration : regionalism and interregionalism in the South Caucasus / Giulia Prelz Oltramonti -- The unintended consequences of neighbourhood policies by the European Union and Russia : region-building in Moldova in an interregional context / Johann Wolfschwenger.
OCLC-licensed vendor bibliographic record.
Keywords: Regionalism -- Case studies; International cooperation -- Case studies; International agencies -- Case studies; POLITICAL SCIENCE / International Relations / General